2017
DOI: 10.1007/s10926-017-9714-1
|View full text |Cite
|
Sign up to set email alerts
|

Common Psychosocial Factors Predicting Return to Work After Common Mental Disorders, Cardiovascular Diseases, and Cancers: A Review of Reviews Supporting a Cross-Disease Approach

Abstract: Purpose This systematic review aimed at identifying the common psychosocial factors that facilitate or hinder the return to work (RTW) after a sick leave due to common mental disorders (CMDs), cardiovascular diseases (CVDs), or cancers (CAs). Methods We conducted a review of reviews searching 13 databases from 1994 to 2016 for peer-reviewed, quantitative, cohort studies investigating factors influencing RTW after a CMD, CVD, or CA. Then, for each disease we identified additional cohort studies published after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
5
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(172 citation statements)
references
References 77 publications
10
140
5
7
Order By: Relevance
“…1 However, we aimed to discuss further considerations that should be taken into account in studies assessing psychosocial determinants of cancer survivors' RTW that include (a) measure prospectively psychological factors within the first year of In epidemiological studies, variables such as cancer-related fatigue or perceived social support have often been assessed using a visual analogue scale or a dichotomous item. 3 These studies do not distinguish how the multiple dimensions of cancer-related fatigue (emotional, physical, and mental fatigue) and perceived social support (emotional, esteem, instrumental, informative, and negative support) could differentially impact cancer survivors' RTW. A recent longitudinal and prospective study, which included 68 women with breast cancer employed at the time of diagnosis, investigated the associations between the multidimensional aspects of fatigue and perceived social support-measured within the year of the breast cancer diagnosis-with RTW.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…1 However, we aimed to discuss further considerations that should be taken into account in studies assessing psychosocial determinants of cancer survivors' RTW that include (a) measure prospectively psychological factors within the first year of In epidemiological studies, variables such as cancer-related fatigue or perceived social support have often been assessed using a visual analogue scale or a dichotomous item. 3 These studies do not distinguish how the multiple dimensions of cancer-related fatigue (emotional, physical, and mental fatigue) and perceived social support (emotional, esteem, instrumental, informative, and negative support) could differentially impact cancer survivors' RTW. A recent longitudinal and prospective study, which included 68 women with breast cancer employed at the time of diagnosis, investigated the associations between the multidimensional aspects of fatigue and perceived social support-measured within the year of the breast cancer diagnosis-with RTW.…”
Section: Commentarymentioning
confidence: 99%
“…First, most such studies assessed psychosocial determinants of RTW between the second and the fifth year after the cancer diagnosis while the majority of patients returned to work within the first year of diagnosis . This retrospective assessment of psychological factors may lead to memory biases which could be avoided if psychological changes due to cancer were assessed prospectively within the first year of diagnosis . Negative memory biases might also be exacerbated following traumatic events, such as a cancer diagnosis .…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…There was moderate evidence that supervisor/co-worker support, work ability, positive RTW expectations, and higher socioeconomic status were facilitators. 13 A small qualitative study reported additional barriers, that is, patients disliking their work, fear of further illness, caring responsibilities at home, employer's sick pay incentivising absence, and inability to contact an occupational physician.…”
Section: Return To Work Barriers and Facilitatorsmentioning
confidence: 99%